EVALUATING ENGLISH SUMMATIVE TEST FOR NINTH GRADE STUDENTS OF SMPS LETJEN S PARMAN MEDAN BASED ON ITEM ANALYSIS - Lastri Prima Sari Sibuea; Anni Holila Pulungan; Syamsul Bahri (Universitas Negeri Medan, 2020)
This research was aimed to explain the indices in evaluating English Summative test based on item analysis. In addition, this research was also aimed to find out the quality of the English Summative test for Ninth Grade Students of SMPS Letjen S Parman Medan based on item analysis, which covers item facility, item discrimination, and distractors efficiency. This research was descriptive-quantitative research. The data were taken from the English Summative Test, answer key, and the students’ answer sheets. The data were collected by documentary technique. There were three indices in evaluating English test based on item analysis, they were: item facility, item discrimination, and distractor efficiency. There was 0% very difficult item, 76% moderate item, and 24% very easy item. Item with negative discrimination were 2.22%, zero discrimination were 6.67%, low discrimination were 20%, moderate discrimination were 60%, and high discrimination were 11.11%. Items with functioned distractors were 42% and items with non-functioned distractors were 58%. The quality of English summative test for ninth grade students of SMPS S Parman was moderate. There were 11.11% good items, 57.78% moderate items, and 31.11% bad items.Keywords: Test, Item Analysis, Item Facility, Item Discrimination, Distractors Efficiency.